2016
DOI: 10.1289/ehp.1409313
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-Related Air Pollution and Parkinson’s Disease in Denmark: A Case–Control Study

Abstract: BackgroundVery little is currently known about air pollutants’ adverse effects on neurodegenerative diseases even though recent studies have linked particulate exposures to brain pathologies associated with Parkinson’s and Alzheimer’s disease.ObjectiveIn the present study, we investigated long-term exposure to traffic-related air pollution and Parkinson’s disease.MethodsIn a case–control study of 1,696 Parkinson’s disease (PD) patients identified from Danish hospital registries and diagnosed 1996–2009 and 1,80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 49 publications
3
100
1
4
Order By: Relevance
“…An increased rate of decline in cognitive function may also be associated with higher air pollution exposures [136]. Some studies have reported associations between exposure to air pollutants and dementia [137, 138], but not all study results support such a relationship [139]. …”
Section: Emerging Adverse Effects Of Outdoor Air Pollutionmentioning
confidence: 99%
“…An increased rate of decline in cognitive function may also be associated with higher air pollution exposures [136]. Some studies have reported associations between exposure to air pollutants and dementia [137, 138], but not all study results support such a relationship [139]. …”
Section: Emerging Adverse Effects Of Outdoor Air Pollutionmentioning
confidence: 99%
“…Few epidemiologic studies have examined the potential roles of ambient air pollutants in PD, and findings are inconsistent (Finkelstein and Jerrett 2007; Kirrane et al 2015; Palacios et al 2014a, 2014b; Ritz et al 2016; Willis et al 2010). Therefore, we investigated the association between ambient PM 10 , PM 2.5 , and nitrogen dioxide (NO 2 ) exposures and risk of PD in the Parkinson’s, Genes and Environment (PAGE) study.…”
Section: Introductionmentioning
confidence: 99%
“…In a nationwide case-control study in Denmark, Ritz et al (39) examined the associations between traffic-related air pollution (represented by NO 2 ) and PD. These authors analyzed exposures to NO 2 , NO x and CO but focused the analysis on NO 2 because of the high inter-correlation between the pollutants and NO 2 being a commonly studied air pollutant.…”
Section: No X No 2 Co and "Traffic Air Pollution"mentioning
confidence: 99%
“…Few of the studies included in this review stratified their analyses by gender or smoking [e.g. Finkelstein and and Jerrett (40), Ritz et al (39), and Palacios et al (35,36,42) stratified by smoking]. In future studies, it would be important to examine the potential interactions between pollutant exposure and gender, smoking, as well as other exposures, such as antioxidants, caffeine, use of NSAID, and other factors.…”
Section: Interactions With Other Environmental Factors Gene-environmmentioning
confidence: 99%